Analisis Kadar Etanol pada Kombucha Tea Biakan Sendiri Berdasarkan Lamanya Waktu Fermentasi - Sri Bulan Nasution; Nikmah Salsabila Pasaribu (An-Najat, 2023)
The stages of kombucha tea fermentation involve the formation of alcohol and acetic acid because symbiotic cultures, especially fungi, break down sugar into alcohol, and the alcohol that is formed will be oxidized by the bacteria Acetobacter xylinum to acetic acid. The purpose of this study was to determine the ethanol content in kombucha tea fermentation based on the length of time of fermentation. This research is an experimental study that was tested in the Laboratory of the Department of Health Medical Laboratory Technology, Poltekkes Kemenkes Medan. The population for this study was tea of the Camellia sinensis species. The research samples included fermented kombucha tea, variant black tea and green tea. The research is a quantitative qualitative study. The qualitative test was carried out using the alcohol Test-Kit Reagent method, the quantitative test was carried out by calculating the percentage of alcohol through heating. Negative alcohol was found in the kombucha tea sample in the first week of fermentation, in the second week of fermentation, positive kombucha tea samples contained alcohol, 0.9% in black tea and 0.2% in green tea; in the third week, an increase in ethanol levels was found, 1% in black tea and 0.7% in green tea.